Genetic Variation of Hemoglobin Gene and Its Impact on Disease Severity - Okab, Hayder Fadhil; Imad Badr Jasim (Universitas Muhammadiyah Sidoarjo, 2025)
Diabetes mellitus is a chronic metabolic disorder characterized by hyperglycemia and associated with severe complications, including neuropathy, nephropathy, and retinopathy. Oxidative stress plays a crucial role in the progression of these complications. Antioxidant enzymes such as superoxide dismutase (SOD), catalase (CAT), and glutathione peroxidase (GPx) are essential in mitigating oxidative stress; however, their activity is often impaired in diabetic patients. Despite global research on oxidative stress in diabetes, there is limited evidence from Iraq examining the relationship between antioxidant enzyme activity and glycemic control. This study aimed to assess the levels of antioxidant enzymes (SOD, CAT, and GPx) and their association with glycemic indices (fasting blood glucose and HbA1c) in patients with type 2 diabetes mellitus compared to healthy controls. A case-control study including 60 diabetic patients and 30 healthy controls revealed significantly reduced activities of SOD, CAT, and GPx in diabetic patients (p < 0.05). In contrast, fasting blood glucose and HbA1c were significantly elevated in diabetic subjects compared to controls. A negative correlation was observed between antioxidant enzyme activity and glycemic indices, indicating that poor glycemic control exacerbates oxidative stress. This is among the first studies in Iraq to demonstrate the association between impaired antioxidant defense mechanisms and hyperglycemia in type 2 diabetes mellitus. The findings emphasize the importance of monitoring oxidative stress biomarkers alongside glycemic indices to improve management strategies and prevent diabetic complications. Highlights: Vitamin D deficiency was prevalent in 62% of patients with type 2 diabetes mellitus. Low vitamin D levels were significantly associated with poor glycemic control and longer disease duration. Age, obesity, and limited sun exposure were identified as key risk factors for vitamin D deficiency in diabetic patients.